Synthesis by combustion in solution of Zn2TiO4+Ag for photocatalytic and photodynamic applications in the visible - Lopera, A. A.; Velasquez, A. M. [UNESP]; Chavarriaga, E. A.; Ocampo, S.; Zaghete, M. A. [UNESP]; Graminha, M. A. [UNESP]; Garcia, C. P.; IOP (Iop Publishing Ltd, 2017)
Zn2TiO4+Ag compounds were synthesized by the solution combustion path seeking to enhance their photocatalytic and photodynamic response in the visible. X-ray diffraction tests confirmed the formation of the phase and the presence of metallic silver. Field emission electron microscopy evidenced the formation of aggregates formed by grains lower than 100nm. The diffuse reflectance tests allowed to detect compound absorption in the visible region and activation energy of 2.8eV. The evaluation of the photocatalytic properties was performed by the degradation of methylene blue while the photodynamic response in biological systems was performed by the antilesihmanicidal response of the compounds in promastigotes of Leishmania amazonensis. Indirect measurement of ROS species confirmed the formation of oxygen singlets and OH radicals of the compounds when subjected to the action of visible light.